Anisotropy evolution of low density polyethylene greenhouse covering films during their service life. (April 2018) - Babaghayou, M.I.; Mourad, Abdel-Hamid I.; Lorenzo, Vicente; Chabira, S.F.; Sebaa, M.
Abstract: The primary focus of this work is to investigate the effect of service life photoageing on the anisotropy of the properties of the low density polyethylene greenhouse covering films. As these films are usually susceptible to mechanical loads in any direction during installation and service, the evaluation of these properties in different directions is of great importance for the greenhouse design and integrity. Unstabilized and stabilized blown extruded single layer films were exposed to natural weathering over several months. The chemical evolution of photooxidation products was evaluated using infrared spectroscopy, the structural evolution was monitored by X-ray diffraction and optical techniques, and the mechanical properties were measured in machine, transverse and intermediate directions. The results indicate that the photoageing significantly increases the film crystallinity, the crystal thickness and the optical birefringence. These structural changes do not only affect the mechanical properties of the film but also the mechanical anisotropy. Highlights: Orientation based mechanical behavior assessment of LDPE greenhouse covering films. Photoageing and processing parameters effect on the properties anisotropy of the LDPE film. Behavior of unstabilized and stabilized films were investigated. The photooxidation significantly increases the film crystallinity and crystal thickness. The photooxidation significantly affects the structural and mechanical anisotropies.